Woman and youth as the citizens of an Islamic government: the Qur’anic perspective and the current realities - Akhmetova, Elmira (2015)
Citizens’ rights of women and youth are enshrined in the Qur’Én. Both men and women, regardless of their age, social class and educational level, are equal as citizens, but not identical, in their rights and responsibilities. This study suggests that Islam has empowered women with the most progressive rights since the seventh century. There was a long line of women scholars and activists who attained high positions and were renowned for their excellence as scholars, social workers, public figures, educators during the time of the Prophet SAW and during the next generations, when Islamic civilisation was flourishing. At the same time, the youth were given full confidence, trust and high responsibilities in power, leadership and decision-making. But this Qur‘Énic empowerment of women and youth, as the paper establishes, bear little relation to the real condition of women and youth in modern Muslim societies. In fact, many problems occurring in the modern Muslim world are related to the ignorance of the rights of women and youth. The post-colonial governments in the MENA region failed to ensure the well-being and security of their citizens; and women are the most suffered stratum from insecurity, domestic abuse, cultural influences, and low access to education and medical care. In addition, Arab youth for decades remained marginalised and isolated and excluded from decision-making. They have been the most frustrated stratum in their societies with the methods of governance. The paper accordingly suggests that the recent outbreak of the Arab Spring is a collective struggle of the masses, especially the youth, for their basic civilian and human rights. Therefore, the paper suggests that governments, in order to achieve stability and prosperity, must ensure a platform for the youth and women to participate in decision-making and to enjoy their rights preserved in Islam.